A Membentuk Generasi Berkarakter: Peran Guru dalam Menumbuhkan Disiplin dan Tanggung Jawab di MI Al Ma’arif Tuban - nurul ngainin (Journal of Education Counseling, 2025)
This study aims to examine the role of teachers in instilling discipline and responsibility in students at MI Al Ma'arif Plandirejo Plumpang, Tuban. The background of this study is based on the phenomenon of declining student discipline and responsibility as seen from lateness, violation of school rules, and low participation in academic and non-academic activities. This study uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results of the study indicate that teachers play a strategic role not only as teachers, but also as mentors, facilitators, and role models in shaping students' character. The implementation of routine activities such as dhuha prayer, tadarus Al-Qur'an, joint prayer, and the habit of maintaining the cleanliness of the school environment have proven effective in shaping students' discipline and responsibility. The instillation of character values ​​is carried out through an exemplary approach, habituation, and giving responsibility to students in various school activities. Thus, the active involvement of teachers in the character formation process greatly contributes to the development of positive and characterful student personalities. Keywords: Role of teachers, discipline, responsibility, character education